Reliability & Sensitivity Analysis of IKR Regional power Network. - Majeed, Asso Raouf (Iraqi Journal for Electrical and Electronic Engineering, 2011)
This paper presents a developed algorithm for reliability sensitivity analysis of engineering networks. Reliability Modeling is proposed for the Iraqi Kurdistan Regional Power Network (IKRPN) using Symbolic Reliability function of the model. The written Pascal code for the developed algorithm finds efficiently path sets and cut sets of the model. Reliability and Unreliability indices are found. The sensitivity of these indices are found with respect to the variation of the network’s elements reliabilities